Weitere vergleichend morphologische Untersuchungen im Formenkreis von Aphis fabae (Homoptera: Aphididae). - Müller, Fritz Paul; Steiner, Hanna (Contributions to Entomology = Beiträge zur Entomologie, 1990)
The host alternating Aphis fabae Scop. sensu stricto, A. fabae cirsiiacanthoidis Scop. and A. fabae solanella Theob., and the autoecious A. fabae evonymi F. are the most abundance representatives of the black bean and beet aphid complex in the territory of the GDR. High-grade morphological conformity combined with hybridization capability justify their arrangement as subspecies. Keys represented in this paper are mainly based on length and number of setae. Three further aphids belong morphologically to the same superspecies. The sexuales of the heteroecious A. mordwilkoi Börner & Janisch may encounter with those of fabae s. str. partly on Viburnum opulus, and Philadelphus coronarius may be settled not only by the sexuales of the mordwilkoi and philadelphi have to receive the rank of subspecies. Aphis armata Hausmann living monophagous on Digitalis, however, must be classified as a sibling species because of reproductive isolation by host limitation.